THE USE OF WORLD GAMES IN THE SPEECH ASKIYA (Scientific journal of the Fergana State University, 2024)
It is known that askiya is among the genres that have risen to the level of art and have not yet lost their value. This genre of folklore is studied in linguistics as an example of word games. Because askiya is based on word games, and it contains words of wit, promptness, grace, and elegance. In this article, the word games that emerged from the words related to the speech of Askiya and Askiya players are analyzed. Several types of puns are analyzed and classified on the example of Askiya text.